2003
DOI: 10.1034/j.1600-0560.2003.00097.x
|View full text |Cite
|
Sign up to set email alerts
|

p53 alterations in porokeratosis

Abstract: p53 alterations can be involved in the pathogenesis of the PK and the carcinogenesis arising in some of the lesions. Since p53 gene inactivation in human cancer is related to mutation and/or loss, the absence of genetic damage could indicate that p53 alterations are only at the protein level, leading to an abnormal cell-cycle control. UV exposure does not seem to play a main role in the process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
36
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 20 publications
(36 reference statements)
0
36
0
Order By: Relevance
“…Mongiat et al [18] demonstrated that knockdown of EMILIN2 increased tumor cell survival, while overexpression impaired tumor cell growth in vitro. Moreover, an increased expression of the p53 tumour suppressor gene product has been found in keratinocytes under or adjacent to the cornoid lamella in all subtypes of porokeratosis [21].…”
Section: Discussionmentioning
confidence: 98%
“…Mongiat et al [18] demonstrated that knockdown of EMILIN2 increased tumor cell survival, while overexpression impaired tumor cell growth in vitro. Moreover, an increased expression of the p53 tumour suppressor gene product has been found in keratinocytes under or adjacent to the cornoid lamella in all subtypes of porokeratosis [21].…”
Section: Discussionmentioning
confidence: 98%
“…Overexpression of p53 has frequently been reported, but is of dubious significance (7). Cyclooxygenase-2 (COX-2) overexpression has also been observed in non-melanic skin tumors and in 20% of PK cases (8).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulated filamentous actin in epidermal cells might disorganize epidermal cell morphogenesis (Kaji et al, 2003;Nishita et al, 2004). The rate of actin polymerization may influence not only the rate of cell division (Pelham and Chang, 2002), but also p53-mediated celluar response to DNA damage (Arranz-Salas et al, 2003;Okorokov et al, 2002), and therefore malignant changes of cells. Our findings suggested that actin cytoskeleton pathway was associated with the pathogenesis of DSAP.…”
Section: Discussionmentioning
confidence: 99%